Town Green area, general view of the Cottage, Brookline, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a house in the Town Green Area of Brookline, Massachusetts. One of several slides taken in this area.; Caption on image: Town Green Area (2) Cottage Walking Tour 1875.; Binder Number 4. Pocket Number: 19.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.